2008
DOI: 10.1080/00207450701591131
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Working Memory Dysfunction in Schizophrenia: An fMRI Investigation

Abstract: Impaired processing of working memory information is one of the cognitive deficits seen in patients with schizophrenia. This study aims at corroborating the differences in the brain activities involved in the process of working memory between patients with schizophrenia and the controls. Twelve patients with schizophrenia and 11 controls participated in the study. Functional magnetic resonance imaging (fMRI) was used to assess cortical activities during the performance of a two-back verbal working memory parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The decreased activation we observed for patients is consistent with some prior research. For example, several investigators have reported decreased activation in prefrontal cortex during an N-back task in individuals with schizophrenia compared to controls (Barch et al, 2001; Pae et al, 2008; Perlstein et al, 2003). Others have reported similar levels of activation between patients and healthy adults when task difficulty is low, but less activation in patients as difficulty increased (Perlstein et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decreased activation we observed for patients is consistent with some prior research. For example, several investigators have reported decreased activation in prefrontal cortex during an N-back task in individuals with schizophrenia compared to controls (Barch et al, 2001; Pae et al, 2008; Perlstein et al, 2003). Others have reported similar levels of activation between patients and healthy adults when task difficulty is low, but less activation in patients as difficulty increased (Perlstein et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that individuals with schizophrenia elicit less brain activation compared to healthy adults during working memory tasks. Using a two-back task with Korean alphabetical letters, individuals with schizophrenia elicited decreased activation in inferior frontal, middle frontal, and superior temporal gyri compared to healthy controls (Pae et al, 2008). Similarly, during an N-back task using English letters patients elicited less activation in right dorsolateral prefrontal cortex (DLPFC) than healthy adults (Perlstein, Dixit, Carter, Noll, & Cohen, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits in WM are widely recognized to play a significant role in the functional outcomes of schizophrenia. Especially, verbal memory deficits are among the most severe cognitive impairments in schizophrenia [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment in schizophrenia predicts poor functional outcome, which is important in theories of the pathogenesis of schizophrenia [1]. To address this issue, numerous functional MRI (fMRI) studies [2][3][4][5] focusing on working memory (WM) have been carried out to identify the neural centers related to cognitive dysfunction in patients with schizophrenia, and it is now well known that cognitive deficits in patients are associated with dysfunction of the dorsolateral prefrontal cortex (dlPFC). Deficits in WM are widely recognized to play a significant role in the functional outcomes of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%